The clinical application of rhBMP-7 for the reconstruction of alveolar cleft. Issue 1 (January 2016) - Ayoub, Ashraf; Roshan, Cherian P.; Gillgrass, Toby; Naudi, Kurt; Ray, Arup
Summary: In this study, radiographic assessment was performed to find out the effectiveness of bone regeneration following the application of recombinant human bone morphogenetic protein 7 (rhBMP-7) for the reconstruction of alveolar cleft defects in 11 cases: nine unilateral and two bilateral alveolar clefs. Reconstruction of the alveolar cleft was performed by using 3.5 mg of rhBMP-7 (Osigraft OP1) on a type I collagen carrier. Radiographs were taken 6 months post operation using a Gendex Intraoral Unit with Agfa Dentus M2 Comfort occlusal film. The amount of bony infill was graded on a Kindelan four-point scale. The patients were followed up for an average of 6.6 years. Based on the radiographic analysis, eight out of the nine unilateral alveolar cleft cases received a score of grade I and one patient had a grade II score, using the Kindelan scale. In the two bilateral alveolar clefts, only one side had bone formation. The radiographic appearance showed a normal trabecular pattern similar to the adjacent bone. Thus, rhBMP-7 was radiographically and clinically successful in regenerating the bone at the alveolar cleft which resulted in shortening of the operation time, absence of donor-site morbidity and a shorter hospital stay. The promising results of this preliminary study should encourage a phase II trial to compare bone grafts with BMP for the reconstruction of alveolar defects.